Effects of the precipitation regimen and spatial scale on the invertebrate communities and ecosystem processes in phytotelmata (2015)
Understanding the factors that drive community stmcture and ecosystem processes are a relevant goal in ecology. One factor is environmental heterogeneity that alters communities through changes in habitat and available resource for species; however, it is unclear if those effects can change according to the spatial scale. Another factor is climate change, which affects community composition and ecosystem functionality through the loss of particular predator species; although, it is unknown if rainfall variability can alter the community and energy and nutrient flux in temporal ecosystems, such as ponds or phytotelmata. We used the community within two phytotelmata, ecological model system in order to assess effect regime on communities and ecosystem processes. bromeliads and tree holes, as an of spatial scale and hydrological regime on communities and ecosystem processes. First, we studied the invertebrate community associated to Guzmania multiflora (André) André ex Mez. (Bromeliaceae) and their biological traits. We assessed the relation between biological traits and habitat complexity and resource availability. We found that habitat complexity not only alters the taxonomical diversity of invertebrates in bromeliads but also their functional diversity tlnough changes in the abundance and richness of biological traits. In this regard, biological traits provide an approach to ecosystem processes and invertebrate adaptations to environmental conditions. Second, we investigated the effects of spatial scale dependence of habitat and detritus on community and decomposition. We found that species turnover of invertebrates associated with free holes depended on a spatial scale and that there was a scale-dependent effect of habitat and litter on the community and litter decomposition. Third, we assessed the relationship between the amount and frequency of precipitation and bromeliad community and functioning. We found that the magnitude of precipitation rather than rainfall frequency affected invertebrate communities, decomposition, and primary productivity. Finally, we analyzed the energy and nitrogen flux in a bromeliad invertebrate food web and its interaction with the loss of an intraguild predator. We found that the interaction between shifts in the amount of precipitation and the presence/absence of the predator altered the energy and nitrogen flow in the bromeliad food web